Peningkatan Mutu Pembelajaran Al-Quran Melalui Metode Drill dan Tadarrus Dalam Kepasihan Bacaan Siswa - agus shalahudin (Pergunu Jawa Barat, 2021)
The theoretical foundation discusses the use of drill method in reading Qur’an. The purpose of this research is to get the picture of planning the implementation and assessment, also to get the picture of the solution conducted to the problem that is faced by using drill method for fluency in reading Qur’an for private MTs students in Bandung City. This method of the research is a qualitative approach and the techniques used in collecting the data are triangulation, observation, interview, and documentation study which the triangulation source was taken from the school principal, teachers and students. The result shows; First, in the aspect of curriculum planning in using Drill Method for MTs Ar-Rosyidiyah and MTs Syamsul ‘Ulum in Bandung City, went to some stages; preparation of the curriculum team, determining the team of supervisors and determining the implementation of time. Second, in the aspect of the implementation of the curriculum in MTs Ar-Rosyidiyah and MTs Syamsul ‘Ulum in Bandung City is using the curriculum implementers are teachers, principals and committees who become partners in controlling and monitoring the curriculum implementation. The implementation plan is prepared by the teacher in the form of targets and learning development plans that are prepared every semester and adjusted to the allocation of time. Third, in the aspect of curriculum evaluation, Bandung City MTs do the five stages, which are: initial evaluation to make curriculum plans, evaluation of curriculum documents or plans, evaluation of curriculum objectives and contents, evaluation of curriculum processes or implementation, evaluation of learning outcomes to see to what extent of learning objectives are achieved, and evaluation of the overall curriculum program, this evaluation is carried out by Madrasah (School) at least once a month, six months and a year. Last, the impact of curriculum implementation is the existence of independence and high authority from the teachers and principals as well as committees in preparing, implementing and evaluating PAI (Religious Lessons) curriculum development activities, increasing fluency in reading the Qur'an, and increasing the ability and skills in memorizing short surah, thus they can practice it in the daily prayer based on their skills of reading and reciting the Qur'an. Key word: Drill Method, Reading, Quran